Dynamic cellular responses to gravitational forces: exploring the impact on white blood cell(s) - Murali, Anirudh; Sarkar, Ram Rup (Biomicrofluidics, 2024)
In recent years, the allure of space exploration and human spaceflight has surged, yet the effects of microgravity on the human body remain a significant concern. Immune and red blood cells rely on hematic or lymphatic streams as their primary means of transportation, posing notable challenges under microgravity conditions. This study sheds light on the intricate dynamics of cell behavior when suspended in bio-fluid under varying gravitational forces. Utilizing the dissipative particle dynamics approach, blood and white blood cells were modeled, with gravity applied as an external force along the vertical axis, ranging from 0 to 2 g in parameter sweeps. The results revealed discernible alterations in the cell shape and spatial alignment in response to gravity, quantified through metrics such as elongation and deformation indices, pitch angle, and normalized center of mass. Statistical analysis using the Mann-Whitney U test underscored clear distinctions between microgravity (<1 g) and hypergravity (>1 g) samples compared to normal gravity (1 g). Furthermore, the examination of forces exerted on the solid, including drag, shear stress, and solid forces, unveiled a reduction in the magnitude as the gravitational force increased. Additional analysis through dimensionless numbers unveiled the dominance of capillary and gravitational forces, which impacted cell velocity, leading to closer proximity to the wall and heightened viscous interaction with surrounding fluid particles. These interactions prompted shape alterations and reduced white blood cell area while increasing red blood cells. This study represents an effort in comprehending the effects of gravity on blood cells, offering insights into the intricate interplay between cellular dynamics and gravitational forces.